[POSTER] Augmented reality for radiation awareness - Leucht, Nicola; Habert, Severine; Wucherer, Patrick; Weidert, Simon; Navab, Nassir; Fallavollita, Pascal (Proceedings of the 2015 IEEE International Symposium on Mixed and Augmented Reality, ISMAR 2015, 2015)
C-arm fluoroscopes are frequently used during surgeries for intraoperative guidance. Unfortunately, due to X-ray emission and scattering, increased radiation exposure occurs in the operating theatre. The objective of this work is to sensitize the surgeon to their radiation exposure, enable them to check on their exposure over time, and to help them choose their best position related to the C-arm gantry during surgery. First, we aim at simulating the amount of radiation that reaches the surgeon using the Geant4 software, a toolkit developed by CERN. Using a flexible setup in which two RGB-D cameras are mounted to the mobile C-arm, the scene is captured and modeled respectively. After the simulation of particles with specific energies, the dose at the surgeon's position, determined by the depth cameras, can be measured. The validation was performed by comparing the simulation results to both theoretical values from the C-arms user manual and real measurements made with a QUART didoSVM dosimeter. The average error was 16.46% and 16.39%, respectively. The proposed flexible setup and high simulation precision without a calibration with measured dosimeter values, has great potential to be directly used and integrated intraoperatively for dose measurement.
CRIS-Team Scopus Importer:2023-03-08
Keywords: Augmented reality; C-arm fluoroscopy; Dose measurement; Radiation exposure; Visualization